Impact of NF-κB pathway on the intervertebral disc inflammation and degeneration induced by over‐mechanical stretching stress - Hui Xu; Guobao Qi; Kunpeng Li; Keshi Yang; Dawei Luo; Zhongxu Cai (BMC, 2021)
Abstract Background Intervertebral disk degeneration (IVDD) contributes to low back pain. Increased cell apoptosis and inflammation, decreased extracellular matrix are associated with IVDD. Nuclear factor-kappa B (NF-κB) signaling pathway and inflammatory cytokines are implicated in the pathophysiology of IVDD. Methods In present study, we established a mechanical stretching stress-stimulated nucleus pulposus (NP) cell model. We knocked down NF-κB p65 by siRNA transfection to inhibit NF-κB and evaluated the effects of NF-κB inhibition on intervertebral disk degeneration. We applied the mechanical stretching stress on NP cells and inhibited NF-κB by siRNA, then evaluated the expression of inflammatory cytokines, matrix metalloproteinase (MMP), aggrecan, collagen II, and monitored viability and apoptosis of NP cells. Results Mechanical stretching stress induced the expression of TNF-α, IL-1β, NF-κB, MMP-3 and MMP-13, while inhibited the production of aggrecan and collagen II in NP cells. Mechanical stretching stress decreased the cell viability and induced apoptosis in NP cells. Inhibition of NF-κB by siRNA suppressed the production of TNF-α, IL-1β, NF-κB, MMP-3 and MMP-13, while upregulated the expression of aggrecan and collagen II in NP cells. Conclusions Inhibition of NF-κB by knocking down p65 suppressed over-mechanical stretching stress-induced cell apoptosis and promoted viability in NP cell. Inhibition of NF-κB suppressed inflammation and degeneration of NP cells in IVDD.